Donor–recipient human leukocyte antigen A mismatching is associated with hepatic artery thrombosis, sepsis, graft loss, and reduced survival after liver transplant. Issue 8 (4th May 2022) - Bricogne, Christopher; Halliday, Neil; Fernando, Raymond; Tsochatzis, Emmanuel A.; Davidson, Brian R.; Harber, Mark; Westbrook, Rachel H.
Abstract: Human leukocyte antigen (HLA) matching is not routinely performed for liver transplantation as there is no consistent evidence of benefit; however, the impact of HLA mismatching remains uncertain. We explored the effect of class I and II HLA mismatching on graft failure and mortality. A total of 1042 liver transplants performed at a single center between 1999 and 2016 with available HLA typing data were included. The median follow‐up period was 9.38 years (interquartile range 4.9–14) and 350/1042 (33.6%) transplants resulted in graft loss and 280/1042 (26.9%) in death. Graft loss and mortality were not associated with the overall number of mismatches at HLA‐A, HLA‐B, HLA‐C, HLA‐DR, and HLA‐DQ loci. However, graft failure and mortality were both increased in HLA mismatching on graft failure and mortality the presence of one ( p  = 0.004 and p  = 0.01, respectively) and two ( p  = 0.01 and p  = 0.04, respectively) HLA‐A mismatches. Elevated hazard ratios for graft failure and death were observed with HLA‐A mismatches in univariate and multivariate Cox proportional hazard models. Excess graft loss with HLA‐A mismatch (138/940 [14.7%] mismatched compared with 6/102 [5.9%] matched transplants) occurred within the first year following transplantation (odds ratio 2.75; p  = 0.02). Strikingly, transplants performed at a single all grafts lost due to hepatic artery thrombosis were in HLA‐A–mismatched transplants (31/940 vs. 0/102), as were those lost due to sepsis (35/940 vs. 0/102). In conclusion, HLA‐A mismatching was associated with increased graft loss and mortality. The poorer outcome for the HLA‐mismatched group was due to hepatic artery thrombosis and sepsis, and these complications occurred exclusively with HLA‐A–mismatched transplants. These data suggest that HLA‐A mismatching is important for outcomes following liver transplant. Therefore, knowledge of HLA‐A matching status may potentially allow for enhanced surveillance, clinical interventions in high‐risk transplants or stratified HLA‐A matching in high‐risk recipients.